Impact of an Antimicrobial Stewardship Program on the Frequency of Drug resistant Bacteria in an Intensive Care Unit - Yadegarynia, Davood; Tehrani, Shabnam; Keyvanfar, Amirreza; Rashidinejad, Somayeh (Novelty in Biomedicine, 2023)
Background: One of the major health problems in the intensive care unit (ICU) is the nosocomial infection caused by multidrug-resistant (MDR) pathogens. The antimicrobial stewardship program (ASP) is a solution to prevent antibiotic resistance. This study aimed to determine the impact of an antimicrobial stewardship program on the frequency of drug-resistant bacteria in an ICU. Materials and Methods: This quasi-experimental study was conducted between 2019 and 2021 in Labbafinejad Hospital, Tehran, Iran. This study consisted of two time periods: 1) one year with no restriction of antibiotic prescription (before ASP), and 2) one year with restriction of antibiotic prescription based on the stewardship program (after ASP). We obtained demographic and clinical characteristics of patients from their medical records. Standard disk diffusion and broth microdilution were used to determine the antibiotic susceptibility of bacterial pathogens isolated from the patients. Results: A total of 300 ICU-admitted patients were included in the study (150 for each period). We found out that the total length of hospitalization, length of hospitalization in ICU, and treatment duration were lower after ASP (P=0.022, P=0.383, and P<0.001, respectively). Also, the frequency of antibiotic resistance, including MDR and Vancomycin-Resistant Enterococci (VRE) strains, decreased significantly after performing ASP (P=0.013). However, in terms of mortality, there was no significant difference between the two periods (P=0.236). Conclusion: The results of our study highlight the implementation of the antibiotic Stewardship program and the rational use of antibiotics in the ICU setting to inhibit the spread of antibiotic-resistant bacteria.